Citizens$1 (Bsatisfaction with the digital land services of Upazila land office: A study of Barishal Sadar Upazila, Bangladeshs - Akter, Marufa (Indian Journal of Public Administration)
At present, Upazila land offices are designated to provide digital land services for reducing the complexity of land-related services and increasing the satisfaction of citizens in Bangladesh. The government has planned to extend the digital land management framework to all Upazila$1 (Bs land offices for improving the state of land service delivery. The study has tried to explore the extent of satisfaction, trust and knowledge of citizens about the digital land services delivered by the Upazila land offices. The study has applied qualitative methodology approach. The data have been collected through in-depth interviews and key-informant interviews, both from service-receivers and service providers. Content analysis has also been used to analyse secondary data. The findings of the study suggest that lack of responsiveness, insincerity and non-cooperation of the staff in service delivery as well as lack of knowledge and awareness of citizens about digital land services are major constraints to achieve satisfaction in digital land administration.- Reproduced s
Keywords: Citizens satisfaction, Service delivery, Responsiveness, Trust, Knowledge, Upazila land office, Bangladesh